2021
DOI: 10.1177/09612033211002275
|View full text |Cite
|
Sign up to set email alerts
|

Plasma checkpoint protein levels and galectin-9 in juvenile systemic lupus erythematosus

Abstract: SLE is a disease of the adaptive immune system where T lymphocyte dysfunction has an important role as well. We assessed the plasma levels of checkpoint receptors expressed on T cells, along with Galectin-9 to reflect type-1 IFN activity and IL-2Rα in childhood SLE patients. Forty-nine children with SLE and15 healthy controls were included. SLEDAI scores were evaluated at the time of sampling. CD25 (IL-2Rα), 4-1BB, B7.2 (CD86), TGF-β1, CTLA-4, PD-L1, PD-1, Tim-3, LAG- 3, Galectin-9 levels were studied by cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Additionally, Hoogen's group showed that Galectin-9 is correlated with disease activity and serves as a reliable and easily measurable serum biomarker for detecting the interferon signature in patients with SLE [108]. Their conclusion is further supported by Yuksel's study, which showed that the serum level of Galectin-9 is correlated with the SLEDAI [109]. The expression of SAMHD1 was also suggested to be associated with the IFN-I signaling pathway.…”
Section: Measurement Of the Activity Of Ifn-i Signaling In Slementioning
confidence: 90%
“…Additionally, Hoogen's group showed that Galectin-9 is correlated with disease activity and serves as a reliable and easily measurable serum biomarker for detecting the interferon signature in patients with SLE [108]. Their conclusion is further supported by Yuksel's study, which showed that the serum level of Galectin-9 is correlated with the SLEDAI [109]. The expression of SAMHD1 was also suggested to be associated with the IFN-I signaling pathway.…”
Section: Measurement Of the Activity Of Ifn-i Signaling In Slementioning
confidence: 90%